An observational study investigating uniformity of manual body condition scoring in dairy cows - Paul, Abhishek; Bhakat, Champak; Mondal, Santu; Mandal, Ajoy (Indian Journal of Dairy Science, 2020)
Body condition scores (BCS) are very useful for dairy herd management but its reliability and consistency of recordings made by observer have been questioned. Moreover, regular high quality manual body condition scoring of an individual cow is difficult as a routine practice in the farm. This study aimed to find out the agreement in BCS within- and between the classifier. An observational study was conducted in which two assessors independently scored BCS of 43 crossbred animals from one dairy hard. Cohenâ€™s kappa (Ðº) and Spearman's rho (Ï) was computed to quantify the agreement between observer for overall BCS measurement and only kappa test for different BCS groups (high, medium and low). For overall BCS score Ðº of 0.62 to 0.71 (p